Renewable Energy Enterprises in Nepal: Growth and Development - Yadav, Maheshwar Prasad; Pradhan, Radhe S. (Journal of Advanced Academic Research, 2017)
Nepal has enormous potential for different kinds of renewable energies; however, biogas, solar and micro-hydro energies are only selected for this study. The study aims at determining growth and development of renewable energy sector and its relationship with renewable energy enterprises in Nepal. This study is based on secondary data covering a period of 37 years of biogas sector, 20 years of solar sector and 50 years of micro-hydro sector. Frequency table, percentage, graph, growth rate and correlation coefficient are employed to analyze the data. The study reveals the largest number of renewable energy enterprises is located in central development region (62.69%) while it is least in far-western region (3.08%) of Nepal. The average growth of biogas, solar and micro-hydro construction companies are 7.96%, 21.18% and 16.07% respectively. The high penetration of biogas plants is in western region while solar home systems are in mid-western region. The highest number of micro-hydro schemes’ installation in term of number and capacity are in eastern and western development region respectively. The result shows that biogas and solar sectors are growing in decreasing trend while micro-hydro sector has ups-down trend. There is significant positive relationship of renewable energy sector with renewable energy enterprises. The study concludes that the growth and development of the renewable energy sector plays a vital role in growth and development of renewable energy enterprises in Nepal. The paper can be extended through investigating characteristics of renewable energy enterprises and renewable energy entrepreneurs to get a greater insight into the results.